2020
DOI: 10.3389/fcell.2020.00316
|View full text |Cite
|
Sign up to set email alerts
|

Limited Potential or Unfavorable Manipulations? Strategies Toward Efficient Mesenchymal Stem/Stromal Cell Applications

Abstract: Despite almost 50 years of research and over 20 years of preclinical and clinical studies, the question of curative potential of mesenchymal stem/stromal cells (MSCs) is still widely discussed in the scientific community. Non-reproducible treatment outcomes or even absence of treatment effects in comparison to control groups challenges the potential of these cells for routine application both in tissue engineering and in regenerative medicine. One of the reasons of such outcomes is non-standardized and often d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…MSCs are becoming increasingly relevant to clinical care [7] but the outcomes associated with MSC treatment have shown great inconsistency. Some of the outcome variability may be due to the altered characteristics associated with the cells, based on the site of isolation of the initial tissue [13,27]. Other factors responsible for inducing variability may include the methods of isolation, the amount of tissue harvested, and the passage number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs are becoming increasingly relevant to clinical care [7] but the outcomes associated with MSC treatment have shown great inconsistency. Some of the outcome variability may be due to the altered characteristics associated with the cells, based on the site of isolation of the initial tissue [13,27]. Other factors responsible for inducing variability may include the methods of isolation, the amount of tissue harvested, and the passage number.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can be harvested from a variety of tissues including adipose tissue, bone marrow, peripheral blood, and umbilical cord [11,12]. Cells from diverse sites have unique properties including basic transcriptome differences and variations in in vitro or in vivo differentiation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Those enzymes have the capacity to degrade collagen and thereby endanger the stability of the early anastomotic closure. It has been shown that immediately after surgery the MMP activity is markedly upregulated [8]. In some early animal studies in rats, unselective MMP inhibition could improve bursting pressures [23].…”
Section: Matrix Metalloproteinase Inhibitionmentioning
confidence: 99%
“…Several molecular classes as growth factors, interleukins, and chemokines mediate communication between immune cells and matrix forming cells. Collagen degrading enzymes, so-called matrix metalloproteinases (MMP), are key players highly active in the early healing phases [8]. Their balanced regulation is important to allow reorganization of collagen without endangering the integrity of the newly formed collagen layer.…”
Section: Introductionmentioning
confidence: 99%
“…From that point on, numerous studies about the handling of these cells have been performed. However, the development of an optimal protocol for cultivating MSCs is still in progress (Spees et al, 2016 ; Lavrentieva et al, 2020 ). The most common and most widely used cell culture medium supplement is fetal calf serum (FCS).…”
Section: Introductionmentioning
confidence: 99%